2022
DOI: 10.3390/cancers14163938
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Effect on Liver Functional Reserve of Atezolizumab and Bevacizumab for Unresectable Hepatocellular Carcinoma in Patients Who Do Not Meet Eligibility Criteria of IMbrave150

Abstract: The IMbrave150 trial demonstrated the high efficacy and safety of atezolizumab and bevacizumab for unresectable hepatocellular carcinoma (HCC). In this multicenter study, the efficacy of this combination and its effect on liver functional reserve were evaluated in patients not meeting the eligibility criteria of IMbrave150. Of 115 patients with unresectable HCC treated with atezolizumab and bevacizumab between October 2020 and January 2022, 72 did not meet the eligibility criteria of IMbrave150, most frequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Moreover, all four studies reported the short-term OR evaluated with mRECIST, and the pooled OR rate was 25% (95% CI, 20-30%, I 2 = 37.64%, p = 0.19, Fig. 2D), while three [24,29,30] of the four studies reported the short-term CR and PR evaluated with mRECIST, and the pooled CR and PR rates were 3% (95% CI, 0-5%, I 2 = 0.00%, p = 0.74, Fig. 3D) and 24% (95% CI, 18-30%, I 2 = 32.04%, p = 0.23, Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 96%
See 4 more Smart Citations
“…Moreover, all four studies reported the short-term OR evaluated with mRECIST, and the pooled OR rate was 25% (95% CI, 20-30%, I 2 = 37.64%, p = 0.19, Fig. 2D), while three [24,29,30] of the four studies reported the short-term CR and PR evaluated with mRECIST, and the pooled CR and PR rates were 3% (95% CI, 0-5%, I 2 = 0.00%, p = 0.74, Fig. 3D) and 24% (95% CI, 18-30%, I 2 = 32.04%, p = 0.23, Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 96%
“…2C). Three [24,29,30] of the four studies reported the short-term CR and PR evaluated with RECIST, and the pooled CR and PR rates were 0% (95% CI, 0-1%, I 2 = 0.00%, p = 0.97, Fig. 3C) and 15% (95% CI, 7-23%, I 2 = 64.79%, p = 0.06, Fig.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 98%
See 3 more Smart Citations